The Cephenniini of China. VIII. New species and new records of Cephennodes Reitter of Hunan, Jiangxi, Zhejian and Fujian (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2016)
Seven new species of Cephennodes Reitter of mainland China are described, all in the nominotypical subgenus: C. brachyspinosus sp. n. (Hunan), C. impressibos sp. n. (Jiangxi), C. hystrix sp. n. (Zhejiang), C. setifer sp. n. (Zhejiang), C. yinziweii sp. n. (Zhejiang), C. datianpingensis sp. n. (Zhejiang), and C. bicribratus sp. n. (Zhejiang). Two species are placed in the Cephennodes bos species group (C. brachyspinosus and C. impressibos), three in the Cephennodes longipes group (C. hystrix, C. setifer and C. yinziweii), and two in a newly established Cephennodes elytratus group (C. datianpingensis and C. bicribratus). Additionally, three previously described species are recorded from new localities: C. capricornis Jałoszyński from Hunan and Zhejiang, C. clypeicornis Jałoszyński from Zhejiang and C. paramerus Jałoszyński from Fujian and Zhejiang. Cephennodes is for the first time reported to occur in Hunan Province.